The Pathology of Coronary Heart Disease - Segal, Bernard L. (1962)
The distribution of coronary atherosclerosis in patients with ischemic heart disease is extensive, and involves at least two major coronary arteries. Thrombosis, occlusion by atheromatous debris and, infrequently, internal hemorrhage may produce final closure of the coronary artery. The anatomy of the coronary vessels, localization of occlusion, recanalization, the extent of intercoronary anastomoses and the physiological demands of the myocardium all affect the ultimate clinical expression of the basic occlusive process.